IMPROVING CONFIDENCE AND ENGLISH LANGUAGE SPEAKING SKILLS USING ROLE PLAY TECHNIQUE WITH TALK SHOW FOR 8th GRADE STUDENTS; A CASE STUDY SMP N 1 KARANGGENENG LAMONGAN - Ninik Setyawati (Edulitics (Education, Literature, and Linguistics) Journal, 2019)
This research aim to improve the taste of the selftconvidenceand Studentsspeaking skill by role play techniques with talk shows in class VIII-A the second semester.in 2018/2019. This research is Class Action Reseach. This reseach consist of 2 cycles. Each cycles consist of four steps. There are planning, implementation,, observation, dan reflection. The subject of reseach is 32 students, class VIII-A the second semester of SMP Negeri 1 Karanggeneng in 2018/2019. The reseach data ia qualitative and quantitave. In the initial condition is showed students speaking skill is same or above minimal completeness of creteria 9stusents showed ( 28.12%) with an average of 63.12 . the first cycles increase tobe 20 students showed (62,50%) with an average 72,71. The first cycles, cocnetive dan fluency of students speaking be increasing. Speaking skill assessment for the second cysles will be increased. It is showed 28 students (87.50%) have gotten score same or above KKM with an average 79.17. increasing is mean that especially for understanding, fluently,and vocabulary aspects. The conclusion of this research is (1) students speaking skills continue to increase and the initial condition fo the first cycle then second cysle: (2) the students of self confidence to speaking in Englsih was increasing.